2007
DOI: 10.1007/s00192-007-0431-8
|View full text |Cite
|
Sign up to set email alerts
|

Urinary incontinence after obstetric anal sphincter injuries (OASIS)—is there a relationship?

Abstract: This study aimed to compare urinary symptoms and its impact on women's quality of life after obstetric anal sphincter injuries (OASIS) with a matched control group in the short term. The study group consisted of 100 primiparous women with OASIS and 104 controls who sustained a second-degree tear or had a mediolateral episiotomy performed. All women completed a validated International Consultation on Incontinence Questionnaire-Short Form (ICIQ-SF) questionnaire 10 weeks after delivery. Compared to controls, sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(29 citation statements)
references
References 30 publications
2
26
1
Order By: Relevance
“…The results of this study suggested that women with anal sphincter disruption had a slightly increased risk of fecal incontinence with no impact on urinary or sexual symptoms and mental or physical health [11]. In contrast, other authors reported a higher incidence of urinary symptoms [12,13] and sexual dysfunction [5,7,14,15] after anal sphincter tear.…”
Section: Introductionmentioning
confidence: 55%
“…The results of this study suggested that women with anal sphincter disruption had a slightly increased risk of fecal incontinence with no impact on urinary or sexual symptoms and mental or physical health [11]. In contrast, other authors reported a higher incidence of urinary symptoms [12,13] and sexual dysfunction [5,7,14,15] after anal sphincter tear.…”
Section: Introductionmentioning
confidence: 55%
“…It is well-established that the prevalence of UI varies greatly depending on study group, definitions and methods used [22]. The prevalence of urinary incontinence during pregnancy is reported to be as high as 44% and between 7% and 34% [22] after delivery.…”
Section: Discussionmentioning
confidence: 99%
“…Overall, we identified 25 studies investigating the impact of obstetric factors on UI after childbirth: 10 cross-sectional studies [35,36,37,38,39,40,41,42,43,44]; 11 cohort studies [45,46,47,48,49,50,51,52,53,54,55]; 3 case-control studies [56,57,58], and 1 quasi-RCT [34]. Perineal tears [41] and episiotomy [34] do not seem to negatively affect urinary continence status at 1 and 4 years [34,41] post partum, respectively.…”
Section: Resultsmentioning
confidence: 99%